IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION SUBJECTIVE AND OBJECTIVE TESTS IN IMPROVING STUDENTS' COGNITIVE ABILITIES (STUDY AT SMA MUHAMMADIYAH 1 KARANGANYAR) - Apriliano, Moza; Anshari, Ari (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
Increasing students' cognitive abilities is a measure of the success of students' understanding in learning, by increasing students' cognitive abilities it is necessary to carry out an evaluation of learning outcomes. In this study, it discusses the need for several tools to measure the level of student success, namely using objective tests and subjective tests. In this study, several forms of objective and subjective tests are presented that can be used by educators who are implemented in learning as well as good levels or standards in their application, of course in terms of implementing objective and subjective tests this has advantages and disadvantages, it is hoped that these advantages and disadvantages can complement each other. The purpose of this research is to identify, develop, improve evaluation instruments in learning Islamic Religious Education, as well as to conduct a study of cognitive domain learning evaluation instruments on objective and subjective tests. The results of this study indicate that the implementation of objective and subjective tests must be in accordance with KKO standards or based on C1-C6 Bloom's Taxonomy to be able to develop students' thinking patterns or levels of thinking in their cognitive.